Efektivitas Penerapan Metode Sorogan Terhadap Keterampilan Membaca Kitab Awamil Mandaya di Pondok Pesantren Daarul Hikmah Jambu Karya Rajeg - Apipah, Paqihatun; Faedurrohman (Penerbit Minhaj Pustaka, 2024)
ABSTRACT Daarul Hikmah Jambu Karya Rajeg Islamic Boarding School is one of the Islamic educational institutions that pays great attention to and prioritizes learning the yellow book, through methods applied in learning to improve the ability to read the yellow book. These methods include sorogan, bandungan, memorization, practice or demonstration. Therefore, the author is interested in conducting research on